The Braconinae (Hymenoptera: Braconidae) of Turkey, with new locality records and descriptions of two new species of Bracon Fabricius, 1804 - Beyarslan, Ahmet; Erdoğan, Özlem Çeti̇n (Zootaxa, 2012)
Two new species, namely Bracon (Bracon) bachtiae Beyarslan sp. n. and Bracon (Glabrobracon) dersimensis Beyarslan sp. n.(Braconinae) collected from Kastamonu and Tunceli provinces of Turkey, are described and compared with related species.Records of 60 Braconinae species collected in different parts of Turkey, especially from the Central and Eastern Anatoliaregions between the years 1980 and 2009, are listed. Thirty-two species are reported as new to Turkey, and new distributional data is added for almost all species.